2021
DOI: 10.1021/acs.biochem.1c00572
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Responses to Iron Withholding by Calprotectin

Abstract: Iron (Fe) plays important roles in both essential cellular processes and virulence pathways for many bacteria. Consequently, Fe withholding by the human innate immune system is an effective form of defense against bacterial infection. In this Perspective, we review recent studies that have established a foundation for our understanding of the impact of the metalsequestering host defense protein calprotectin (CP) on bacterial Fe homeostasis. We also discuss two recently uncovered strategies for bacterial adapta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 92 publications
0
10
0
Order By: Relevance
“…We show here that the Δ mtsA mutant strain is more susceptible to chelation by calprotectin than WT GBS, and while supplementation of extracellular Mn 2+ rescues growth of calprotectin-treated WT GBS, the Δ mtsA mutant strain remains susceptible to chelation despite Mn 2+ supplementation. While our work has focused on the role of MtsA in Mn 2+ homeostasis, in light of previous work showing the ability of calprotectin to also induce iron stress ( 61 63 ) and knowledge that expression of the GBS mtsABC locus is induced under both Mn 2+ and iron limitation ( 64 ), it will be of interest to examine whether the mtsABC locus is also involved in iron uptake and how this might contribute to GBS colonization of the FRT.…”
Section: Discussionmentioning
confidence: 99%
“…We show here that the Δ mtsA mutant strain is more susceptible to chelation by calprotectin than WT GBS, and while supplementation of extracellular Mn 2+ rescues growth of calprotectin-treated WT GBS, the Δ mtsA mutant strain remains susceptible to chelation despite Mn 2+ supplementation. While our work has focused on the role of MtsA in Mn 2+ homeostasis, in light of previous work showing the ability of calprotectin to also induce iron stress ( 61 63 ) and knowledge that expression of the GBS mtsABC locus is induced under both Mn 2+ and iron limitation ( 64 ), it will be of interest to examine whether the mtsABC locus is also involved in iron uptake and how this might contribute to GBS colonization of the FRT.…”
Section: Discussionmentioning
confidence: 99%
“…A large body of literature has demonstrated that A . baumannii is transcriptionally responsive to nutrient metal sequestration by host metalloproteins such as calprotectin [ 23 26 , 57 59 ], as well as to iron and copper stress, both in vitro and in vivo [ 79 92 ]. We therefore hypothesized that nutritional immunity may play an essential role in the innate immune response to this pathogen and sought to further investigate these processes during infection.…”
Section: Resultsmentioning
confidence: 99%
“…Calprotectin (CP) was originally identified to be involved in Mn 2+ limitation by the host, but was more recently found to bind Fe 2+ efficiently in the presence of Ca 2+ ( Nakashige et al, 2015 ). It has been demonstrated that CP induces Fe starvation in S. aureus cultures ( Obisesan, Zygiel, and Nolan 2021 ; Zygiel et al, 2021 ). The ability of S. aureus to efficiently incorporate heme affords protection against CP induced Fe starvation ( Zygiel et al, 2021 ).…”
Section: Overcoming Reduced Iron Availabilitymentioning
confidence: 99%